2023
DOI: 10.1093/braincomms/fcad117
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation for post-COVID fatigue: a randomized, double-blind, controlled pilot study

Abstract: Fatigue is one of the most frequent and disabling symptoms of post-COVID syndrome. In this study, we aimed to assess the effects of transcranial direct current stimulation on fatigue severity in a group of patients with post-COVID syndrome and chronic fatigue. We conducted a double-blind, parallel-group, sham-controlled study to evaluate the short-term effects of anodal transcranial direct current stimulation (2 mA, 20 min/day) on the left dorsolateral prefrontal cortex. The Modified Fatigue Impact Scale score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“… 97 Conversely, a study conducted in Spain found that eight sessions of tDCS targeting the left dorsolateral prefrontal cortex were effective for the treatment of physical fatigue but had no effect on cognition in post-COVID patients with fatigue. 98 Two studies conducted in Germany and Brazil proposed a 3-week and 4-week neuromodulation therapy course, respectively, consisting of tDCS-assisted cognitive training in PCCD, with cognitive performance as the primary outcome ( NCT04944147 , NCT05389592 ). 99 Another study in Hong Kong, China, is currently testing the effects of transcranial pulse stimulation (TPS) for young adults with depression after the COVID-19 pandemic, with cognitive function as a secondary outcome ( NCT05006365 ).…”
Section: Current Status Of Managementmentioning
confidence: 99%
“… 97 Conversely, a study conducted in Spain found that eight sessions of tDCS targeting the left dorsolateral prefrontal cortex were effective for the treatment of physical fatigue but had no effect on cognition in post-COVID patients with fatigue. 98 Two studies conducted in Germany and Brazil proposed a 3-week and 4-week neuromodulation therapy course, respectively, consisting of tDCS-assisted cognitive training in PCCD, with cognitive performance as the primary outcome ( NCT04944147 , NCT05389592 ). 99 Another study in Hong Kong, China, is currently testing the effects of transcranial pulse stimulation (TPS) for young adults with depression after the COVID-19 pandemic, with cognitive function as a secondary outcome ( NCT05006365 ).…”
Section: Current Status Of Managementmentioning
confidence: 99%
“…This may suggest common mechanisms and neural underpinnings in fatigue and cognitive dysfunction in both disorders, as has been recently described 9 . This opens the way to test new therapies for fatigue based on their association with functional brain changes, such as non-invasive brain stimulation, which have shown positive effects in two clinical trials 47 , 48 . However, at the same time, the lower correlation with neuropsychological tests and the greater severity of fatigue in PCC suggest the existence of other mechanisms (probably not dependent on the central nervous system and including systemic processes such as immune mechanisms, mitochondrial dysfunction or muscle abnormalities) involved in the pathophysiology of fatigue in PCC 24 , 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the current clinical trials have rapidly accumulated, some treatments (e.g., transcranial direct current stimulation) have demonstrated efficacy on fatigue in post-COVID patients. Therefore, we might consider 3-arm RCT to compare the effectiveness of acupuncture, sham acupuncture and usual care ( 33 ).…”
Section: Discussionmentioning
confidence: 99%